Evaluasi Pengelolaan Obat pada Puskesmas di Kota Pariaman - Syukriati Chaira; Erizal Zaini; Trisfa Augia (Jurnal Sains Farmasi & Klinis, 2016)
Drug Management at health centers need to be well, because exellent drugs management will ensure the continuity of availability and affordability of drugs that are efficient, effective and rational. This study aims to determine drugs management at seven community health centers in Pariaman, based indicators of drugs management stipulated by Ministry Health of Republic Indonesia. This research is descriptive-evaluative, with quantitative and qualitative methods, using retrospective data in 2013 and 2014. The results showed that suitability of drug provided by DOEN 64.70%-73.51%, accuracy of drug demand, 2:28%-24.47%, accuracy of drug distribution 4.66% -35.59%, percentage of drugs that are not prescribed, 5:00%-23.49%, percentage of prescribing generic drugs 97.27% -100%, percentage differences in recording of stock card with amount of physical drugs, 0.00%-13.13%, it can be concluded that drugs management at health centers in Pariaman is not good, because it is not accordance with established standards.